PERAN GURU KELAS SEBAGAI FASILITATOR DALAM MEMBANGUN LINGKUNGAN BELAJAR DI SD SUPRIYADI 02 SEMARANG - Eva Khoirunnisa; Joko Sulianto; Qoriati Mushafanah; Karsono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The teacher acts as a facilitator in building an appropriate learning environment. The teacher as a facilitator supports learning activities in facilitating learning activities for students. In facilitating these needs the teacher creates a supportive learning environment so that it can be carried out. With the learning environment can achieve the goals that have been planned. The purpose of this study was to determine the role of the classroom teacher as a facilitator in building a learning environment. This study uses qualitative research methods, by conducting observation, interviews, and documentation. The results obtained in this study, teaching and learning activities in class III B the teacher has played the role as it should, namely as a facilitator in building a learning environment by creating a sense of security, comfort, and implementing group activities, with a learning environment that supports students having the courage to convey opinion or opinion